KOORDINASI PEMERINTAH DAERAH DALAM PENANGGULANGAN RENDAHNYA PEMBAYARAN PAJAK BUMI DAN BANGUNAN PERDESAAN PERKOTAAN (PBB-P2) (Studi di Desa Ukui II Kecamatan Ukui Kebupaten Pelalawan) - Muliadi, Jefri; Amin, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Submission of matters concerning taxation of the earth and rural and urban buildings (PBB-P2) to the Regency / City Government has become the responsibility for the Regional Government, in particular to contribute to the increase of local revenues (PAD). Likewise with the Pelalawan District Government, one of the districts that have received the abundance of tax affairs of the earth and rural and urban buildings (PBB-P2). Since the delegation of authority, Pelalawan Regency Government has not been able to optimize the revenue from PBB-P2 sector. This can be seen from the number of PBB-P2 receipts, especially in Ukui Ukui II Subdistrict that did not meet the target. This paper put forward a qualitative approach with descriptive data analysis and reference theory of coordination and supervision.The results of this study indicate that (1) coordination in the handling of tax payments of land and rural and urban buildings is only implemented in the form of socialization of PBB-P2 to the community by the Regional Revenue Service so that it impacts the organization's coverage in collecting data, collection and evaluation of target. Meanwhile, at the sub-district level, the sub-district head is given the additional task of coordinating with the village head and village heads in relation to the submission of the PBB-P2 SPPT without being authorized to collect and prosecute, and (2) related to the findings, which impedes the implementation of the coordination of the PBB-P2 by PBB Division BPHTB Regional Revenue Office of Pelalawan Regency is related to obstacles not evaluated, obstacles of leadership style (procedural bureaucracy), administrative barriers and social and cultural barriers.Keywords: Coordination, Supervision, tax of the earthand buildings